Deformable high-niobium TiAl alloy with optimized high-temperature creep resistance and preparation method thereof

Through the forging process, the composition and processing process of high-niobium TiAl alloy is optimized, and the problem of insufficient high-temperature creep resistance caused by B2 phase in TiAl alloy is solved, which significantly improves the deformation ability and creep resistance of the alloy, and achieves the fine grain size and improved microstructure, improving performance in high temperature applications.

CN119307782APending Publication Date: 2025-01-14HARBIN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411430042.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The B2 phase in the existing TiAl alloy is not conducive to the high-temperature creep resistance, resulting in insufficient deformation ability under high-temperature conditions.

Method used

The composition and processing process of high niobium TiAl alloy is optimized through the forging process, and axial compression and deformation is carried out using vacuum arc smelting and thermal simulation test machines to adjust the microstructure of the alloy, increase the content of the γ phase and change the form of yttrium compound, thereby improving the alloy High temperature creep resistance.

Benefits of technology

It significantly improves the steady-state creep strain rate of high niobium TiAl alloy at 800℃, reduces the creep strain rate, improves the deformation ability and creep resistance of the alloy, and has simple process and high efficiency, and has low equipment requirements. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119307782A_ABST
    Figure CN119307782A_ABST
Patent Text Reader

Abstract

The invention discloses a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance and a preparation method of the deformed high-niobium TiAl alloy, relates to the deformed high-niobium TiAl alloy with the optimized high-temperature creep resistance and the preparation method of the deformed high-niobium TiAl alloy, and aims to solve the problem that a B2 phase in an existing TiAl alloy is not beneficial to the high-temperature creep resistance. The preparation method comprises the following steps: smelting raw materials by adopting a vacuum arc smelting furnace to prepare an alloy ingot; and the alloy ingot is axially compressed on a Gleeble thermal simulation testing machine, the strain rate is set to be 0.01 s <-1 >, compression is conducted at 1320 DEG C, and the deformation amount is 75%. The deformed high-niobium TiAl alloy prepared through the method has an ultra-fine grain structure and twisted B2 phases and lamellar colonies, the creep resistance of the high-niobium TiAl alloy is optimized, and the method is applied to the field of metal materials and preparation of the metal materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of economy and science and technology, my country's modern industry and science and technology have gradually entered a new stage of development. Higher efficiency and better biocompatibility have become new propositions for material development. Advanced material design concepts revolve around higher service temperatures, faster operating speeds, and lighter weight. With the rapid development of my country's aerospace industry, higher requirements have been put forward for the design of aircraft engines. At the current stage, reducing its own weight is one of the main development directions of aircraft engines. By reducing the weight of the engine, the thrust-to-weight ratio of the aircraft engine can be improved to improve economic and utilization benefits. Therefore, the development of a new type of lightweight, high-strength, high-temperature resistant structural material is of great significance to the development of aircraft vehicles.

[0003] TiAl intermetallic compounds have long-range ordered atomic arrangement, metallic bonds and covalent bonds coexist in the crystal, and have the characteristics of metals and ceramics. They are a new type of lightweight heat-resistant structural material with broad application prospects in the fields of aerospace and civil industry. Adding appropriate alloying elements to TiAl-based alloys and regulating their organization is one of the effective methods to improve their room temperature and high temperature mechanical properties. With the development of alloying of TiAl-based alloys, adding high melting point solid solution elements such as Nb, Cr, V, Mo, and Mn to them can improve the high temperature oxidation resistance and creep resistance of TiAl alloys. At the same time, these elements can promote the retention of β phase to room temperature and transform into an ordered B2 phase. When the matrix contains more B2 phase, the B2 phase is not conducive to the mechanical properties of the alloy, especially the high temperature creep resistance.

[0004] Some TiAl alloy systems have been put into practical use, replacing nickel-based high-temperature alloys. The low-pressure turbine blades developed are used in aircraft engines, which can not only effectively improve the aircraft's cruising range, but also make progress in engine noise reduction and flight performance improvement, and have been successfully applied. At present, in actual production, TiAl aircraft engine blades are mainly cast, but forged blades have the characteristics of high strength, dense structure and customizability that cast blades do not have, which can effectively improve the coarse segregation alloy structure. Therefore, the present invention aims to improve the creep resistance of high niobium TiAl alloys by forging. Summary of the invention

[0005] The purpose of the present invention is to solve the problem that the B2 phase in the existing TiAl alloy is not conducive to high temperature creep resistance, and to provide a deformed high niobium TiAl alloy with optimized high temperature creep resistance and a preparation method thereof.

[0006] The invention discloses a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance, which is composed of 44% Al, 6% Nb, 0.1-0.3% B, 0.1-0.3% Y, 0.2-0.4% W and the balance Ti in atomic percentage.

[0007] The present invention provides a method for preparing a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance, which is carried out according to the following steps:

[0008] 1. Weighing metal single substance particles according to the atomic percentage of 44% Al, 6% Nb, 0.1-0.3% B, 0.1-0.3% Y, 0.2-0.4% W and the balance Ti to obtain a raw material;

[0009] 2. Using a vacuum arc melting furnace to melt the raw materials and prepare alloy ingots;

[0010] 3. The alloy ingot is axially compressed on a thermal simulation test machine, and the strain rate is set to 0.01s -1 , compressed at 1320℃ with a deformation of 75%, then kept warm, and then cooled to room temperature with the furnace to prepare a deformed high-niobium TiAl alloy with optimized creep resistance.

[0011] The present invention has the following beneficial effects:

[0012] 1. The present invention provides a deformed high-niobium TiAl alloy with optimized creep resistance and a preparation method thereof, introduces the deformation method into the performance optimization of the high-niobium TiAl alloy, has a simple preparation process and high process efficiency, and provides a practical basis for improving the hot processing performance of the TiAl alloy.

[0013] Second, the present invention uses a hot deformation processing method to prepare an alloy with a fine grain size, changes the phase composition in the microstructure, and the increase in the γ phase improves the deformation ability of the alloy; adjusts the lamellar structure and the existence form of yttrium in the alloy, and at the same time alleviates the large degree of segregation problem in the cast alloy, and improves the high-temperature creep resistance of the alloy. The creep strain rate of the deformed alloy in the steady state stage at 800°C and 125MPa is 0.013% / h, and the creep strain rate of the alloy in the steady state stage is greatly reduced.

[0014] 3. The solidification and processing technology of the alloy in the present invention has low requirements on equipment, simple process steps, good experimental stability and high repeatability. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 The xrd spectra of the modified high niobium TiAl alloy prepared in Example 1 and the cast high niobium TiAl alloy prepared in the comparative example; 1 is the comparative example and 2 is the example;

[0016] Figure 2 The microstructure diagrams are of the deformed high niobium TiAl alloy prepared in Example 1 and the as-cast high niobium TiAl alloy prepared in the comparative example; 1 is the comparative example and 2 is the example;

[0017] Figure 3 The creep curves of the deformed high niobium TiAl alloy prepared in Example 1 at 780-820°C and 125-175Mpa respectively;

[0018] Figure 4 The apparent creep activation energy Q and the apparent creep stress index fitting calculation curve of the deformed high niobium TiAl alloy prepared in Example 1;

[0019] Figure 5 The creep curves are of the deformed high niobium TiAl alloy prepared in Example 1 and the cast high niobium TiAl alloy prepared in the comparative example; 1 is the comparative example and 2 is the example. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.

[0021] Specific implementation method 1: This implementation method is a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance, which is composed of 44% Al, 6% Nb, 0.1-0.3% B, 0.1-0.3% Y, 0.2-0.4% W and the remainder Ti in atomic percentage.

[0022] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the deformed high niobium TiAl alloy is composed of 44% Al, 6% Nb, 0.2% B, 0.2% Y, 0.3% W and 49.3% Ti in atomic percentage. The rest is the same as specific embodiment 1.

[0023] Specific implementation method three: This implementation method is a method for preparing a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance, which is carried out according to the following steps:

[0024] 1. Weighing metal single substance particles according to the atomic percentage of 44% Al, 6% Nb, 0.1-0.3% B, 0.1-0.3% Y, 0.2-0.4% W and the balance Ti to obtain a raw material;

[0025] 2. Using a vacuum arc melting furnace to melt the raw materials and prepare alloy ingots;

[0026] 3. The alloy ingot is axially compressed on a thermal simulation test machine, and the strain rate is set to 0.01s -1, compressed at 1320℃ with a deformation of 75%, then kept warm, and then cooled to room temperature with the furnace to prepare a deformed high-niobium TiAl alloy with optimized creep resistance.

[0027] Specific embodiment 4: This embodiment is different from specific embodiment 3 in that: Step 2 is a method for preparing alloy ingots using a vacuum arc melting furnace: placing raw materials into a copper crucible of a vacuum melting furnace, evacuating the vacuum furnace, and then filling with argon gas for protective melting, and after cooling, a button ingot is obtained, and then the button ingot is repeatedly melted 4 to 6 times, and cooled to obtain an alloy ingot. The rest is the same as specific embodiment 3.

[0028] Specific implementation method 5: This implementation method is different from specific implementation method 3 or 4 in that: vacuum is pumped to 3×10 - 3 The rest of the invention is the same as the third or fourth embodiment.

[0029] Specific implementation method 6: This implementation method is different from any one of specific implementation methods 3 to 5 in that argon gas is filled to 0.05 MPa, and the rest is the same as any one of specific implementation methods 3 to 5.

[0030] Specific embodiment 7: This embodiment is different from specific embodiments 3 to 6 in that the raw materials are placed in the crucible in the order of melting point from low to high during smelting. The rest is the same as specific embodiments 3 to 6.

[0031] Specific embodiment 8: This embodiment is different from specific embodiments 3 to 7 in that the button ingot is repeatedly smelted 5 times and cooled to obtain an alloy ingot. The rest is the same as specific embodiments 3 to 7.

[0032] Specific embodiment 9: This embodiment is different from specific embodiments 3 to 8 in that: during the smelting process, the current needs to be maintained at 500-600A, and after it becomes molten, it is continued to be smelted at 500-600A for 3 minutes, and then reduced to 0A at a rate of 50A every 10 seconds. Others are the same as specific embodiments 3 to 8.

[0033] Specific embodiment 10: This embodiment differs from any one of specific embodiments 3 to 9 in that: Step 3: Before compression, vacuumize to 10 -3 Pa, and then 50 Pa of argon is introduced. The rest is the same as any one of the third to ninth embodiments.

[0034] The following examples are used to verify the beneficial effects of the present invention:

[0035] Example 1: A method for preparing a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance, wherein the chemical formula is Ti-44Al-6Nb-0.2B-0.2Y-0.3W, and the specific steps are as follows:

[0036] (1) According to the chemical formula of the alloy Ti-44Al-6Nb-0.2B-0.2Y-0.3W, the mass ratios are converted into 53.14% Ti, 27.88% Al, 17.44% Nb, 0.86% B, 0.05% Y, and 0.62% W. The experimental raw materials are weighed according to the mass percentage. When weighing, the oxidation and burning of the alloy during the smelting process are considered, and the burning amount is applied as 5%. Therefore, the actual weight is weighed according to 105% of the nominal mass of each alloy.

[0037] (2) The alloy ingot is obtained by vacuum non-consumable arc melting. The weighed raw materials are placed in the crucible in the order of melting point from low to high (the order of placement from the bottom is: Al, Y, Ti, B, Nb, W). The vacuum degree in the furnace is maintained at 3×10 3 Pa vacuum environment, and then filled with 0.05MPa argon as a protective atmosphere. Before the start of smelting, first melt 80g of titanium in another crucible to absorb the remaining oxygen in the furnace to ensure the smelting quality in the subsequent smelting process. During the smelting process, the alloy is destined to be smelted repeatedly 5 times. Before each remelting, the alloy button ingot needs to be turned over by a robotic arm to ensure that the composition of the alloy ingot is uniform. During the smelting process, the current needs to be maintained at 500-600A. After it is molten, continue to melt at 500-600A for 3 minutes, and then reduce it to 0A at a rate of 50A every 10 seconds to discharge the gas in the ingot and eliminate defects in the smelting process as much as possible. Finally, an alloy button ingot with a diameter of 5cm and a thickness of 1cm is obtained;

[0038] (3) The alloy button ingot obtained by smelting is cut into cylindrical specimens with a diameter of 6 mm and a height of 9 mm by electric spark wire cutting, and the specimens are polished with 400#, 800#, 1200#, and 2000# sandpaper to remove surface impurities, and ultrasonically cleaned, and then a thermocouple is welded to the center of the side of the cylindrical specimen for subsequent axial compression deformation;

[0039] (4) Use the Gleeble thermal simulation test machine to gradually compress the two circular end faces toward the thermocouple and evacuate to 10 -3 After the temperature reaches 1000 ℃, 50Pa of argon gas is introduced, and then the sample is compressed at 1320℃ with a deformation of 75%. After keeping the temperature for 30 minutes, the sample is cooled to room temperature with the furnace to prepare a deformed high niobium TiAl alloy with optimized creep resistance.

[0040] Comparative Example 1

[0041] A method for preparing a cast high-niobium TiAl alloy, the chemical formula of which is Ti-44Al-6Nb-0.2B-0.2Y-0.3W, comprises the following specific steps:

[0042] (1) According to the chemical formula of the alloy Ti-44Al-6Nb-0.2B-0.2Y-0.3W, the experimental raw materials were weighed according to the mass percentage. When weighing, the oxidation and burning of the alloy during the smelting process were taken into account, and the burning amount was applied as 5%. Therefore, the actual weight was weighed according to 105% of the nominal mass of various alloys.

[0043] (2) The alloy ingot is obtained by vacuum non-consumable arc melting. The weighed raw materials are placed in the crucible in the order of low to high melting points. The vacuum degree in the furnace is maintained at 3×10 3 Pa vacuum environment, and then filled with 0.05MPa argon as a protective atmosphere. Before the start of smelting, first melt 80g of titanium in another crucible to absorb the remaining oxygen in the furnace to ensure the smelting quality in the subsequent smelting process. During the smelting process, the alloy is destined to be smelted repeatedly 5 times. Before each remelting, the alloy ingot needs to be turned over by a robotic arm to ensure that the composition of the alloy ingot is uniform. During the smelting process, the current needs to be maintained at 500-600A. After it is molten, continue to melt at 500-600A for 3 minutes, and then reduce it to 0A at a rate of 50A every 10 seconds to discharge the gas in the ingot and eliminate defects in the smelting process as much as possible. Finally, an alloy button ingot with a diameter of 5cm and a thickness of 1cm is obtained.

[0044] Figure 1 The XRD patterns of the deformed high-niobium TiAl alloy prepared in Example 1 and the cast high-niobium TiAl alloy prepared in the comparative example show that the peak intensity of the γ phase in the alloy increases after the deformation treatment. In the alloy system, the γ phase has more slip systems that can be activated, so the γ phase exhibits better plastic deformation ability at both room temperature and high temperature, and therefore, the creep performance of the deformed alloy is improved.

[0045] Figure 2 The microstructure diagrams of the deformed high-niobium TiAl alloy prepared in Example 1 and the cast high-niobium TiAl alloy prepared in the comparative example. It can be seen that the grain size in the microstructure of the alloy after deformation treatment is reduced; the lamellar structure in the alloy presents a twisted shape; the yttrium morphology becomes needle-rod-shaped; and the segregation in the alloy is alleviated. The refinement of the grain size can increase the grain boundary area, hinder the dislocation movement during the deformation process, and thus improve the creep resistance of the alloy. The twisted lamellar structure of the alloy and the needle-rod-shaped yttrium also become sites that hinder dislocation movement and crack initiation and development, which is also beneficial to the improvement of the creep resistance of the alloy.

[0046] Figure 3Creep curves of the deformed high niobium TiAl alloy prepared in Example 1 at 780-820°C and 125-175Mpa. Based on the steady-state creep strain rate shown in the creep curves of the alloy measured under different conditions, the Dohn law is used for calculation to obtain Figure 4 The apparent creep activation energy Q and the apparent creep stress index fitting calculation curve of the modified high niobium TiAl alloy prepared in Example 1. The apparent creep activation energy of the modified alloy is Q = 211.5 KJ / mol, and the apparent creep stress index is n = 3.89. Therefore, the creep mechanism of the modified alloy is the dislocation slip mechanism.

[0047] Figure 5 The creep curves of the deformed high niobium TiAl alloy prepared in Example 1 and the cast high niobium TiAl alloy prepared in the comparative example. It can be seen from the creep curves that both the cast alloy and the deformed alloy have the characteristics of power-law creep. It can be seen from the creep curves measured at 800°C and 125MPa that the creep strain rate of the deformed alloy in the steady-state stage is 0.013% / h, and the creep strain rate of the cast alloy in the steady-state stage is 0.035% / h. It can be seen that the creep strain rate of the alloy in the steady-state stage after deformation treatment is greatly reduced.

Claims

1. A deformed high niobium TiAl alloy with optimized high temperature creep resistance, characterized in that: The deformed high-niobium TiAl alloy consists of 44% Al, 6% Nb, 0.1-0.3% B, 0.1-0.3% Y, 0.2-0.4% W and the balance Ti in atomic percentage.

2. A deformed high niobium TiAl alloy with optimized high temperature creep resistance according to claim 1, characterized in that: The wrought high-niobium TiAl alloy consists of 44% Al, 6% Nb, 0.2% B, 0.2% Y, 0.3% W and 49.3% Ti in atomic percentage.

3. A method for preparing a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance as claimed in claim 1, characterized in that: The preparation method is carried out according to the following steps:

1. Weighing metal single substance particles according to the atomic percentage of 44% Al, 6% Nb, 0.1-0.3% B, 0.1-0.3% Y, 0.2-0.4% W and the balance Ti to obtain a raw material; 2. Using a vacuum arc melting furnace to melt the raw materials and prepare alloy ingots; 3. The alloy ingot is axially compressed on a thermal simulation test machine, and the strain rate is set to 0.01s -1 , compressed at 1320℃ with a deformation of 75%, then kept warm, and then cooled to room temperature with the furnace to prepare a deformed high-niobium TiAl alloy with optimized creep resistance.

4. The method for preparing a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance according to claim 1, characterized in that: Step 2: The method for preparing the alloy ingot using a vacuum arc melting furnace is as follows: the raw materials are placed in a copper crucible of the vacuum melting furnace, evacuated and filled with argon gas for protective melting, and after cooling, a button ingot is obtained, and then the button ingot is repeatedly melted 4 to 6 times and cooled to obtain the alloy ingot.

5. The method for preparing a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance according to claim 3, characterized in that: Vacuum to 3×10 -3 Pa.

6. The method for preparing a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance according to claim 3, characterized in that: Fill with argon to 0.05MPa.

7. The method for preparing a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance according to claim 3, characterized in that: During smelting, the raw materials are placed in the crucible in order from low to high melting points.

8. The method for preparing a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance according to claim 3, characterized in that: The button ingot was repeatedly smelted 5 times and cooled to obtain an alloy ingot.

9. The method for preparing a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance according to claim 3, characterized in that: During the smelting process, the current needs to be maintained at 500-600A. After it becomes molten, continue to smelt at 500-600A for 3 minutes, and then reduce it to 0A at a rate of 50A every 10 seconds.

10. The method for preparing a deformed high-niobium TiAl alloy with optimized high-temperature creep resistance according to claim 1, characterized in that: Step 3: Vacuum to 10 before compression -3 Pa, and then 50 Pa of argon was introduced.